2021
DOI: 10.1155/2021/8029180
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of IL-33 Gene Correlated with Renal Allograft Fibrosis in Kidney Transplant Recipients

Abstract: Background. Nowadays, renal allograft survival is confined by the development of allograft fibrosis. Previous studies have reported interleukin-33 (IL-33) upregulated significantly in patients with chronic renal allograft dysfunction, and it could induce renal tubular epithelial to mesenchymal transition (EMT), which eventually contributed to renal allograft fibrosis. Our study intended to detect the underlying association between single nucleotide polymorphisms (SNPs) of IL-33 gene and renal allograft fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the context of the kidney, IL-33 has been implicated in the development and progression of several diseases etiologies, including acute kidney injury, CKD, glomerulonephritis, and renal allograft fibrosis. 38 , 40 , 50 , 74 , 75 , 76 , 77 , 78 In several mouse models of renal disease, blocking IL-33 has also been shown to reduce disease severity. 74 , 75 , 79 , 80 , 81 Our investigation of IL-33 in DKD has provided additional insight into the important immunomodulatory effect of this alarmin.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the kidney, IL-33 has been implicated in the development and progression of several diseases etiologies, including acute kidney injury, CKD, glomerulonephritis, and renal allograft fibrosis. 38 , 40 , 50 , 74 , 75 , 76 , 77 , 78 In several mouse models of renal disease, blocking IL-33 has also been shown to reduce disease severity. 74 , 75 , 79 , 80 , 81 Our investigation of IL-33 in DKD has provided additional insight into the important immunomodulatory effect of this alarmin.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the continuous variables, we included the indicators in a sequential manner in a model that used the adjusted confounding factors based on the relative degree of their connection with allograft fibrosis. In our previous study, the administration of sirolimus was identified as the confounding factor by the GLM analysis, which suggests that sirolimus treatment significantly affects the severity of fibrosis in renal grafts (21). Next, after using the Bonferroni correction to adapt the various sirolimus treatments (adjusted P=0.005), a multiple inheritance model analysis was performed for each of the 5 analytical models (i.e., the dominant, recessive, additive, overdominant, and codominant models) to investigate the association between these MMP tagger SNPs and renal graft fibrosis after kidney transplantation (Table S3).…”
Section: Multiple Inheritance Model Analysismentioning
confidence: 99%
“…of Nanjing Medical University who underwent kidney transplantation from February 2010 to December 2015 were recruited for this study. The inclusion and exclusion criteria were described in our previous related study (21). Medical information, including each recipient's age, sex, weight, demographic details, the cause of the kidney disease, serum creatinine, and human leukocyte antigen (HLA) mismatch, were extracted from hospital records.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%